Menumbuhkan Jiwa Wirausaha Mahasiswa Peserta Pengenalan Kehidupan Kampus bagi Mahasiswa Baru (PKKMB) Sekolah Tinggi Ilmu Administrasi Satya Negara Palembang - Aryanisila; Holipah; Asmawati; Yofitri Heny Wahyuli (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2023)
PKKBM is a stage in preparing new students to go through the transition process to become mature and independent students, as well as a catalyst in the process of adapting students to a new environment and providing provisions for their success in studying at tertiary institutions, especially at STIA Satya Negara Palembang. The purpose of this service is to instill awareness of the nation, state and state defense, as well as concern for the environment and society, introduce learning systems and the life of the academic community by instilling basic educational values, introducing rights and obligations as students, creating a friendly campus ( inclusive), safe, and healthy and shape the character of students who prioritize attitudes as intellectuals who rely on intelligence and maturity. This service uses a participatory approach using the method of conveying knowledge from resource persons, delivering PKKMB material, observations and interviews from various sources during the Entrepreneurship Bazaar, showcasing the talents of new students in vocal, dance, recitation and martial arts. The results of the dedication show that PKKMB participants know business opportunities, are good at communicating, and are confident in promoting their products during the bazaar.